Attitudes and experiences of nurses in the implementation of 24-hours on call strategy in Greater Tzaneen Sub-District Clinics, Mopani District, Limpopo Province - Nyathi, Thembelihle Brigitte (My University, 2016)
The purpose of this study was to determine the attitudes and experiences of nurses when implementing the 24-hour on call strategy in clinics. A quantitative descriptive research was conducted. A stratified random sampling approach was used to divide the nurse’s population into homogeneous strata from which elements were selected randomly. Three groups of respondents participated in the study, namely, professional nurses (n=99), enrolled nurses (n=32) and enrolled nursing assistants (n=35). The study highlighted the areas that the respondents felt needed to be strengthened in order to provide quality care when implementing the strategy. The findings revealed that there were some personal and management factors that needed to be addressed and improved in order to ensure continuity of services to the communities in rural areas. The study also identified positive areas which the respondents felt supported the implementation of the strategy. KEY CONCEPTS 24-hour on call strategy, Integrated Primary Health care approach, experience, attitudes.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Integrated Primary Health care approach; Nurses' experiences; Nurses' attitudes; Nurses -- Attitudes -- South Africa -- Limpopo; Health facilities -- South Africa -- Limpopo; Hours of labor -- South Africa -- Limpopo